Importance of lipid microdomains, rafts, in absorption, delivery, and biological effects of resveratrol. (15th July 2013) - Delmas, Dominique; Aires, Virginie; Colin, Didier J.; Limagne, Emeric; Scagliarini, Alessandra; Cotte, Alexia K.; Ghiringhelli, François
Abstract : The preventive effects of the phytoalexin trans ‐resveratrol toward cancer have been largely described at the cellular and molecular levels in both in vivo and in vitro models; however, its primary targets are still poorly identified. In this review, we show the crucial role of cell membrane microdomains, that is, lipid rafts, not solely in the initiation of the early biochemical events triggered by resveratrol leading to cancer cell death, but also in resveratrol absorption and distribution. Resveratrol accumulates in lipid rafts and is then taken up by cells through raft‐dependent endocytosis. These events allow early activation of kinase pathways and redistribution of cell death receptors within lipid microdomains, events ultimately leading to apoptotic cell death.